Nonerythropoietic Erythropoietin Mimetic Peptide ARA290 Ameliorates Chronic Stress-Induced Depression-Like Behavior and Inflammation in Mice - Xu, Guanglei; Zou, Tao; Deng, Lijiao; Yang, Guang; Guo, Tingting; Wang, Yi; Niu, Chunxiao; Cheng, Qianqian; Yang, Xiqin; Dong, Jie; Zhang, Jiyan (Frontiers in Pharmacology, 2022)
Major depressive disorder (MDD) is a highly prevalent psychiatric disorder. But the treatment of depression remains challenging. Anti-inflammatory treatments frequently produce antidepressant effects. EPO-derived helix-B peptide ARA290 has been reported to retain the anti-inflammatory and tissue-protective functions of EPO without erythropoiesis-stimulating effects. The effects of ARA290 on MDD remains elusive. This study established chronic unpredictable mild stress (CUMS) and chronic social defeat stress (CSDS) depression-like mouse models. Daily ARA290 administration during chronic stress induction in two mouse models ameliorated depression-like behavior, similar to fluoxetine. With marginal effects on peripheral blood haemoglobin and red cells, ARA290 and fluoxetine reversed chronic stress-induced increased frequencies and/or numbers of CD11b+Ly6Ghi neutrophils and CD11b+Ly6Chi monocytes in the bone marrow and meninges. Furthermore, both drugs reversed chronic stress-induced microglia activation. Thus, ARA290 ameliorated chronic stress-induced depression-like behavior in mice through, at least partially, its anti-inflammatory effects.